Remote Impact of the Equatorial Pacific on Florida Current Transport. Issue 4 (15th February 2022) - Dong, Shenfu; Volkov, Denis L.; Goni, Gustavo; Pujiana, Kandaga; Tagklis, Filippos; Baringer, Molly
Abstract: Satellite and in‐situ measurements are used in this study to investigate a possible link between the Florida Current transport (FCT) and temperature changes in the equatorial Pacific. Consistent with the geostrophic nature of the current, the FCT variability shows good correspondence with the changes in sea surface height differences ( ∆ SSH) between the eastern (SSHeast ) and western (SSHwest ) sides of the Florida Straits. While the variability of SSHwest is mostly associated with seasonal and shorter timescale fluctuations of ∆ SSH and FCT, changes in SSHeast are strongly related to the interannual variability of ∆ SSH and FCT. A significant correlation is found between the FCT and the Oceanic Niño Index (ONI) on interannual timescales, which explains 21% of the interannual FCT variance. The connection of ONI with FCT is through its impact on SSHeast, associated with the anomalous convergence/divergence in the Caribbean region and the Bahamas forced by ONI‐induced wind stress curl changes. Plain Language Summary: Variations in the Florida Current transport (FCT) have been linked to widespread weather and climate phenomena. Various driving mechanisms for the FCT variability have been proposed, but none can fully explain its wide spectrum variability. In this study, we analyzed in‐situ and satellite observations and found a linear link between the FCT and temperature changes in the equatorial Pacific on interannual timescales. A warming condition in the equatorial Pacific results in low pressure anomalies in the Gulf of Mexico and high pressure anomalies extended into the Caribbean Sea from the tropical Atlantic. This atmospheric pressure pattern is associated with anticyclonic winds over the Caribbean Sea and the Bahamas that drive anomalous oceanic convergence and, therefore, cause higher sea levels in those regions. A higher sea level near the Bahamas often steepens the sea level slope across the Florida Straits, which corresponds to a stronger FCT. A cooling condition in the equatorial Pacific will have the opposite effect, resulting in a reduced FCT. Key Points: Interannual variations in Florida Current transport are highly correlated with sea level at eastern side of the Florida Straits (SSHeast ) Changes in SSHeast exhibit a linear link to warming and cooling conditions in the equatorial Pacific This connection is through the wind stress curl changes remotely forced from the equatorial Pacific